علم الطبقات وأبعادها الحضارية = Reading the Tabaqat genre in biographical literature - Jamil, Khairil Husaini (2019)
The paper consists of an introductory section and pages from several works in tabaqat literature produced by early scholars in hadith and several other disciplines of Islamic scholarship.